Instrumental use of marine bacteria to stimulate growth in seaweed - Mien, Pham Thi; Minh-thu, Phan; Ngoc Trieu, Bui Thi; Hieu, Nguyen Minh; Ha, Dao Viet (Journal of Agricultural Sciences, 2024)
Marine bacteria are being considered for research and application in medicine, industry, and aquaculture. Bacterial strains derived from the edible algae Caulerpa lentillifera and corals were screened for the production of indole-3-acetic acid (IAA) - a phytohormone of the auxin group. The ability of phosphate solubilization and antimicrobial activities of IAA-producing strains were also implemented in this study. The potent strains were identified by 16sRNA sequencing. The isolate RN06 produced a high amount of IAA, used inorganic phosphate, and inhibited Bacillus subtilis ATCC6633, Escherichia coli O157, and Serratia marcescens PDL100. The IAA producing HRA5 isolated from the hard coral proved phosphate solubilization ability, and showed antimicrobial activity against B. subtilis. Morphology analysis and 16sRNA sequencing revealed that the isolate RN06 was the nearest strain to Bacillus amyloliquefaciens, and HRA5 was affiliated with Pseudomonas sp. The comprehensive report delves into the isolation of bacteria extracted from edible seaweed and corals sourced from the expansive Vietnamese sea. These isolated bacteria strains stand as promising and potentially pivotal subjects for further investigation into the development of microbial fertilizers catered specifically for seaweed farming.